Efektivitas Perangkat Pembelajaran Biologi Berorientasi Model Problem Based Learning Bermuatan Karakter Ditinjau Dari Segi Aktivitas Siswa - Afza, Aulia; Razak, Abdul; Ananda, Azwar (Universitas PGRI Sumatera Barat, 2017)
The purpose of this research is to produce biology learning materials oriented by Problem Based Learning (PBL) model containing character on circulation system topic for senior high school in terms of student activities. This research is a development research using Plomp development model. This model consists of 3 phases, namely preliminary research, prototyping stage, dan assessment phase. Previous research has been done in practicality test at assessment phase. In this study continued on the assessment phase, namely effectiveness test in terms of student activities. The study was conducted in student of second years which one of Senior High School in Indonesia. The research instrument used observation sheet of student activity. Data analysis techniques using the formula percentage. The results showed that the average value of student activity was 94.05 with very effective category. It can be concluded that biology learning material oriented by PBL model containing character on circulation system topic for senior high school has been effective in terms of student activity